VASCULAR AND NERVOUS CHANGES IN DENTAL PULP OF HUMAN TEMPORARY TEETH ASSOCIATED WITH THE PHYSIOLOGICAL ROOT RESORPTION PROCESS - Couve, Eduardo; Escudero, Diego; Orellana, Macarena; Encalada, Daniela (Applied Sciences in Dentistry, 2020)
Objective: To determine vascular and nervous changes during the progression of physiological root resorption, in three stages. Materials and methods: 21 healthy temporary canines with indication of extraction, conducted on the Faculty of Dentistry of the University of Valparaiso were analyzed. Samples were processed for indirect immunofluorescence using Alexa Fluor 488 goat anti-mouse fluorochromes for Schwann cells (CS); Alexa fluor 555 goat anti-rabbit for endothelium. By confocal microscopy, a subodontoblastic portion, greater than the amelocemental junction, and an apical portion related to the root resorption area were analyzed. They were classified in initial, middle, and advanced stages. To process images, Ez-C1 3.90 and ImageJ programs were employed, and through visual analysis, researchers described pulpal changes. Results: As the tooth was resorbed, nervous tissue degraded and disorganized with angiogenesis around it during middle stage. The same was observed in the coronal section, but with more predominance in the apical section. As physiological root resorption happened, the vascularity of temporary teeth increased. Conclusion: As physiological root resorption ensues, simultaneously occurs degradation and disorganization of nervous tissue, along with angiogenesis.